2021
DOI: 10.1177/10887679211048492
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Intimate Partner Homicide: The Long Road Ahead

Abstract: Intimate partner homicide (IPH) consists primarily of men killing women in the context of intimate partner violence. Researchers have described and identified risk factors associated with IPH; additional comprehensive data collection is needed to better understand IPH risk and to develop risk-informed prevention. Due to structural racism, available interventions within the criminal legal and social service systems may be eschewed by those—such as Black women—who are at the highest risk. Anti-racist research, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 78 publications
(99 reference statements)
0
13
0
Order By: Relevance
“…External issues, such as negative police encounters, systemic discrimination, and a lack of cultural responsiveness further compound with the internal challenges (T. B. Bent-Goodley, 2013; Messing et al, 2022; N. M. St. Vil et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…External issues, such as negative police encounters, systemic discrimination, and a lack of cultural responsiveness further compound with the internal challenges (T. B. Bent-Goodley, 2013; Messing et al, 2022; N. M. St. Vil et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additional studies have found that survivors in the Black community often first reach out to informal supports, such as family, friends, and faith-based organizations, before or even if they seek help from formal systems such as law enforcement and domestic violence service providers (T. Bent-Goodley et al, 2012; Harper, 2022; Messing et al, 2022; Waller et al, 2022). As a result, survivors exhaust a number of resources to identify how and when to obtain support (Evans & Feder, 2016; Thomas et al, 2015; Zosky, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In the FBI data, the spousal category includes common-law marriages, and the category of boyfriend or girlfriend excludes homosexual relationships. There are a variety of limitations to these data(Langford, Isaac, and Kabat, 1998;Messing et al, 2022).…”
mentioning
confidence: 99%